Calm to chaos: Engaging undergraduate nursing students with the complex nature of interruptions during medication administration - Hayes, Carolyn; Jackson, Debra; Davidson, Patricia M.; Daly, John; Power, Tamara (Journal of clinical nursing, 2017)
Aims and Objectives To describe undergraduate student nurse responses to a simulated role‐play experience focussing on managing interruptions during medication administration. Background Improving patient safety requires that we find creative and innovative methods of teaching medication administration to undergraduate nurses in real‐world conditions. Nurses are responsible for the majority of medication administrations in health care. Incidents and errors associated with medications are a significant patient safety issue and often occur as a result of interruptions. Undergraduate nursing students are generally taught medication administration skills in a calm and uninterrupted simulated environment. However, in the clinical environment medication administration is challenged by multiple interruptions. Design/Methods A qualitative study using convenience sampling was used to examine student perceptions of a simulated role‐play experience. Data were collected from 451 of a possible 528 student written reflective responses and subject to thematic analysis. Results Students reported an increased understanding of the impacts of interruptions while administering medications and an improved awareness of how to manage disruptions. This study reports on one of three emergent themes: “Calm to chaos: engaging with the complex nature of clinical practice.” Conclusions Interrupting medication administration in realistic and safe settings facilitates awareness, allows for students to begin to develop management strategies in relation to interruption and increases their confidence. Students were given the opportunity to consolidate and integrate prior and new knowledge and skills through this role‐play simulation.